Hubungan Lama Operasi dengan Kejadian Shivering Pada Pasien Pasca Spinal Anestesi Di RSUD Meuredu Kabupaten Pidie Jaya Aceh - Zulfikar, Zulfikar; Sumarni, Tri; Kurniawan, Wasis Eko (Universitas Harapan Bangsa Purwokerto, 2023)
Shivering events after anesthesia can cause patients to feel uncomfortable or even painful due to stretching of the surgical scar and increased oxygen demand due to increased muscle activity. The purpose of this study was to determine the relationship between the duration of surgery and the incidence of shivering in post-spinal anesthesia patients at Meureudu Hospital, Pidie Jaya District, Aceh. This study uses an analytic method that is cross sectional. The sampling technique in this study was carried out using a purposive sampling technique of 65 respondents. The instrument in this study used an observation sheet containing the length of operation and shivering. Data analysis was performed univariately and bivariately using the chi-square test. The results showed that of the 65 respondents, most of them underwent surgery quickly, as many as 29 respondents (44.6%), most of the post-spinal anesthesia patients at Meuredu Hospital, Pidie Jaya Regency, did not experience shivering, as many as 33 respondents (50.8%). the chi-square test showed that there was a relationship between length of operation and the incidence of shivering in post-spinal anesthesia patients with a p value of 0.001 (p <0.05). The conclusion of this study is that there is a relationship between the duration of surgery and the incidence of shivering in post-spinal anesthesia patients at Meureudu Hospital, Pidie Jaya District